CRITERIA FOR ALLOCATION OF INTERNATIONAL RESPONSIBILITY BETWEEN THE EUROPEAN UNION AND ITS MEMBER STATES - Pažereckaitė, Gintarė (Teisė, 2015)
The article aims to determine criteria for allocation of international responsibility between the European Union (EU) and its Member States. Firstly, rules on responsibility of the international organizations presented in the Draft articles of the International Law Commission are discussed. Further, the article examines how judicial bodies decide cases related to international responsibility of the EU in different areas of law. Finally, possible formation of lex specialis in case of the EU is assessed and the following three criteria for attribution of conduct and allocation of international responsibility between EU and its Member States are identified: i) nature of EU competence, ii) actors, and iii) remedies.It is concluded that in the areas of exclusive competence, a conduct of EU organs or agents is always attributable to the EU. Whereas in areas of shared competence, a decisive factor is an actor who performs specific conduct. In order to decide on attribution of conduct to the EU or its Member States, the effective control criteria should be followed. Furthermore, especially in the area of human rights, the existence of remedies and their nature prevailing in the particular legal regime are significant factors. Therefore in order to ensure the proper protection of rights of third parties and proper functioning of the specific legal regime, courts may apply international responsibility to the EU Member States even in cases when they are implementing EU law.